A review of radiation-induced lymphopenia in patients with esophageal cancer: an immunological perspective for radiotherapy. (May 2020) - Wang, Xin; Wang, Peiliang; Zhao, Zongxing; Mao, Qingfeng; Yu, Jinming; Li, Minghuan
Radiotherapy is a frequently utilized therapeutic modality in the treatment of esophageal cancer (EC). Even though extensive studies are carried out in radiotherapy for EC, the design of the clinical target volume and the radiation dose is not satisfactorily uniform. Radiotherapy acts as a double-edged sword on the immune system; it has both an immunostimulatory effect and an immunosuppressive effect. Radiation-induced lymphopenia and its potential association with tumor control and survival outcomes remain to be understood. The advent of immunotherapy has renewed the focus on preserving a pool of functioning lymphocytes in the circulation. In this review, we summarize the potential impact mechanisms of radiotherapy on peripheral blood lymphocytes and the prognostic role of radiation-induced lymphopenia in patients with EC. We also propose the concept of organs-at-risk of lymphopenia and discuss potential strategies to mitigate its effects on patients with EC. From an immunological perspective, we put forward the hypothesis that optimizing radiation modalities, radiation target volume schemes, and radiation doses could help to reduce radiation-induced lymphopenia risks and maximize the immunomodulatory role of radiotherapy. An optimized radiotherapy plan may further enhance the feasibility and effectiveness of combining immunotherapy with radiotherapy for EC.